Effects of proteasome inhibitor MG-132 on the parasite Schistosoma mansoni. - Enyara R Morais; Katia C Oliveira; Renato G de Paula; Alice M M Ornelas; Érika B C Moreira; Fernanda Rafacho Badoco; Lizandra G Magalhães; Sergio Verjovski-Almeida; Vanderlei Rodrigues (PLoS ONE)
Proteasome is a proteolytic complex responsible for intracellular protein turnover in eukaryotes, archaea and in some actinobacteria species. Previous work has demonstrated that in Schistosoma mansoni parasites, the proteasome inhibitor MG-132 affects parasite development. However, the molecular targets affected by MG-132 in S. mansoni are not entirely known. Here, we used expression microarrays to measure the genome-wide changes in gene expression of S. mansoni adult worms exposed in vitro to MG-132, followed by in silico functional analyses of the affected genes using Ingenuity Pathway Analysis (IPA). Scanning electron microscopy was used to document changes in the parasites' tegument. We identified 1,919 genes with a statistically significant (q-value ≤ 0.025) differential expression in parasites treated for 24 h with MG-132, when compared with control. Of these, a total of 1,130 genes were up-regulated and 790 genes were down-regulated. A functional gene interaction network comprised of MG-132 and its target genes, known from the literature to be affected by the compound in humans, was identified here as affected by MG-132. While MG-132 activated the expression of the 26S proteasome genes, it also decreased the expression of 19S chaperones assembly, 20S proteasome maturation, ubiquitin-like NEDD8 and its partner cullin-3 ubiquitin ligase genes. Interestingly, genes that encode proteins related to potassium ion binding, integral membrane component, ATPase and potassium channel activities were significantly down-regulated, whereas genes encoding proteins related to actin binding and microtubule motor activity were significantly up-regulated. MG-132 caused important changes in the worm tegument; peeling, outbreaks and swelling in the tegument tubercles could be observed, which is consistent with interference on the ionic homeostasis in S. mansoni. Finally, we showed the down-regulation of Bax pro-apoptotic gene, as well as up-regulation of two apoptosis inhibitor genes, IAP1 and BRE1, and in contrast, down-regulation of Apaf-1 apoptotic activator, thus suggesting that apoptosis is deregulated in S. mansoni exposed to MG-132. A considerable insight has been gained concerning the potential of MG-132 as a gene expression modulator, and overall the data suggest that the proteasome might be an important molecular target for the design of new drugs against schistosomiasis.